STUDI TENTANG KORELASI ANTARA PREFERENSI PEMBAYARAN DENGAN VARIABEL SOSIAL DEMOGRAFI - Widiyati, Sri; Listyani, Theresia Tyas; Rois, Muhammad (KEUNIS, 2022)
The era of digitalization is underway in Indonesia. One of the influential aspects is the business environment. In the business world, economic transaction are vital in developing a cashless society. The purposed of the study to assess the socio demographic variables (gender, marital status, education level, occupation dan income) correlate of the payments preferences. The sampling method was purposive sampling. An online survey of 100 participants  was conducted   among a sample of people who aged 20 years and over and have used e-money for three months. The survey included two parts: first, socio demographic characteristics and second the preferency of payments. Cross tabulation and Chi Squared test were used. The results showed that the majority participans was under 40 years old and have more one instruments of e-money. E-money used for on line shopping, transportation and to pay the bills. The conclution of the study there was no significant correlation between the preference of payment methods with socio demographic variables.